Hubungan Kebiasaan Minum Teh dan Pengetahuan Gizi dengan Kadar Hemoglobin Pada Siswi Di SMK Negeri 1 Sukoharjo Kabupaten Sukoharjo - Suni, Syahrizal Rahman, Dwi Sarbini, S.ST., M.Kes, dr. Listiana D.S, M.Si (2016)
Introduction : Anemia is still one health problem in adolescents in Indonesia. Adolescent girls are at risk of developing anemia than young men. Anaemia in adolescents can affect learning concentration resulting in decreased performance at school. Anemia is caused by several things, such as the lack of knowledge of nutrition will be the selection of foods that contain iron and consumption of tea contains tannin which can inhibit iron absorption. The aim of research to determine the relationship of tea drinking habits and nutrition knowledge with hemoglobin levels at State Vocational High School 1 of Sukoharjo. The purpose of the research was to determine the correlation between tea drinking habits and nutrition knowledge of anemia among female students at State Vocational High School 1 of Sukoharjo. Research Methodes : The research used cross-sectional design. The total subjects were 62 female students, who were selected through systematic proportional random sampling of all female students in class XI who had qualification of inclution and exlution criterias. Nutritional knowledge and tea drinking habits was obtained by questionnaire. Hemoglobin were obtained using the HemoCue . Data were analyzed with Rank Spearman Correlation test. Result : A total of 37.1% of the subjects suffered from anemia. Most subjects (53,2%) had a rarely habit of drinking tea (<200 ml/day) 53.2%. A total of 54.8% of subjects had a less knowledge of nutrition. Bivariate a test results showed that the p-value a tea drinking habits and hemoglobin levels is 0.001; r= -0.463, the p-value nutrition knowledge and hemoglobin levels is 0.012; r= 0.316 Conclusion : There was correlation between tea drinking habits and hemoglobin levels. There was correlation between nutritional knowledge and hemoglobin levels. Keywords : anemia, a tea drinking habits, hemoglobin, iron, nutritional knowledge, tannin Bibliography : 38 : 1983 - 2015